A significant feature in the general relativistic time evolution of the redshift of photons coming from a star orbiting Sgr A*. (22nd October 2019) - Saida, Hiromi; Nishiyama, Shogo; Ohgami, Takayuki; Takamori, Yohsuke; Takahashi, Masaaki; Minowa, Yosuke; Najarro, Francisco; Hamano, Satoshi; Omiya, Masashi; Iwamatsu, Atsushi; Takahashi, Mizuki; Gorin, Haruka; et al.
Abstract: The star S0-2, orbiting the Galactic central massive black hole candidate Sgr A^*, passed its pericenter in 2018 May. This event is the first chance to detect the general relativistic (GR) effect of a massive black hole, free from non-gravitational physics. The observable GR evidence in the event is the difference between the GR redshift and the Newtonian redshift of photons coming from S0-2. Within the present observational precision, the first post-Newtonian (1PN) GR evidence is detectable. In this paper, we give a theoretical analysis of the time evolution of the 1PN GR evidence, under a presupposition that is different from used in previous papers. Our presupposition is that the GR/Newtonian redshift is always calculated with the parameter values (the mass of Sgr A^*, the initial conditions of S0-2, and so on) determined by fitting the GR/Newtonian motion of S0-2 with the observational data. It is then revealed that the difference of the GR redshift and the Newtonian one shows two peaks before and after the pericenter passage. This double-peak appearance is due to our presupposition, and reduces to a single peak if the same parameter values are used in both GR and Newtonian redshifts as considered in previous papers. In addition to this theoretical discussion, we report our observational data obtained with the Subaru telescope by 2018. The quality and the number of Subaru data in 2018 are not sufficient to confirm the detection of the double-peak appearance.